Mathematical Modeling as a Aspect for Designing Agricultural Machines and Units (Development History Of Southern Urals Scientific School) - Yu. S. Tsench; E. V. Godlevskaya (Сельскохозяйственные машины и технологии)
This research paper examines the findings presented in the doctoral and PhD theses from the Southern Urals scientific school specifically focusing on the design process of tillage machines and units through the application of mathematical modeling. (Research purpose) The objective of the study is to identify the patterns in designing tillage machines and units and, based on these patterns forecast their potential enhancements using mathematical modeling. (Materials and methods) The paper analyses the creation of mathematical models based on field tests of tillage machine under diverse soil and climatic conditions emphasizing the authors’ optimal design and upgrade decisions (Results and discussion) The research reveals that the design process of soil-cultivating machines progressed through such stages as: empirical design, computational experimentation and the use of computer-aided design. The evolutionary development of research tools demonstrates a gradual convergence between the mathematical models and the actual working conditions of tillage machines and units. Consequently, this enables the improvement and substantiation of tillage machine parameters to meet specific quality criteria for the tillage process, as well as the development of adaptable crop cultivation technologies applicable to various regions’ soil and climatic conditions. (Conclusions) The study concludes that to enhance the performance of tillage machines and units and achieve the desired quality parameters, further research should focus on machine computer-aided design, including the design of vibratory working bodies, utilization of compressed air and electromagnetic fields, creation of highly automated soil-cultivating machines capable of adjusting to specified working conditions, and development of remote control systems for managing tillage and sowing machine operations.